"Using the other side of my brain": creativity in the research classroom. Issue 3 (2nd July 2016) - Benton, Amy D.; Russell, Amy
ABSTRACT: The purpose of this paper is to present the outcomes of integrating student creative projects in social work research methods classes as a strategy to increase student engagement. Researchers propose that integration of literary arts into courses that students sometimes find daunting will provide an alternative to traditional modes of education, thus enhancing opportunities for student learning. Results from a qualitative classroom study will be presented to show student interpretation of their own creative projects and student evaluations of the assignment. Implications for social work education will be offered.